Gastrointestinal parasitic burdens in UK tortoises: a survey of tortoise owners and potential risk factors. (30th November 2013) - Hedley, J.; Eatwell, K.; Shaw, D. J.
Abstract : Despite gastrointestinal parasites being commonly diagnosed in captive tortoises throughout the UK, there is a lack of data regarding the prevalence. The aims of this study were to investigate the prevalence of gastrointestinal parasites in tortoises in the UK, and to investigate the factors affecting the prevalence of these parasites. Owners were invited to submit a faecal sample from their tortoise in conjunction with a completed questionnaire covering details of signalment and husbandry. Data from the questionnaires were analysed at the end of the study. Faecal analysis was performed on samples from Testudo hermanni, Testudo graeca and Testudo horsfieldii . This involved examination of direct wet preparations, a modified McMaster technique, passive NaCl flotation and Cryptosporidium staining. Of the 142 samples used, 130 were examined by the first three methods. 49 per cent were positive for one or more parasites. Of the positive samples, 67 per cent were positive for oxyurids, 28 per cent were positive for ascarids and 28 per cent were positive for protozoa ( Balantidium, Nyctotherus or flagellates). Only 1/113 (0.8 per cent) samples was positive for Cryptosporidium. The most important risk factors for parasites were sex (F) and length of time (<5 years) in owner's possession. This survey showed that gastrointestinal parasites are frequently detected in the faecal samples of captive tortoises in the UK, but their prevalence may be influenced by various factors including sex, length of time owned, age and species.